The association between XRCC1 Arg399Gln polymorphism and risk of leukemia in different populations: a meta-analysis of case-control studies - Wang, Fang (Onco Targets Ther, 2015)
BACKGROUND: Associations between Arg399Gln single-nucleotide polymorphism (SNP) in the XRCC1 gene and leukemia susceptibility have been studied extensively, however, the results are inconsistent. The aim of this study was to determine these associations using meta-analytical methods. METHODS: A meta-analysis was performed to examine the associations between XRCC1 Arg399-Gln SNP and leukemia risk. A literature search of PubMed and Web of Science databases was conducted to identify relevant studies published up to March 10, 2015. The references of the retrieved articles were also screened. All the statistical analyses were conducted using Review Manager software. RESULTS: The XRCC1 Arg399Gln SNP was found to be associated with increased childhood risk of acute lymphoblastic leukemia among Asians under the dominant (odds ratio [OR] 2.11, 95% confidence interval [CI] 1.50–2.97, P<0.0001), allele contrast (OR 1.72, 95% CI 1.33–2.23, P<0.0001), and homozygote contrast (OR 2.34, 95% CI 1.25–4.36, P=0.008) models. However, no association was found in Caucasians between the SNP and risk of either chronic myeloid leukemia or chronic lymphocytic leukemia under any contrast model. CONCLUSION: The findings of the current meta-analysis indicate that the XRCC1 Arg399Gln SNP is a risk factor for childhood lymphoblastic leukemia in Asians.